Gender Mix and Team Performance: Differences between Exogenously and Endogenously Formed Teams - Ainoa Aparicio Fenoll; Sarah Zaccagni (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We conduct a randomized controlled trial to study the effect of gender composition of teams on performance, self-concept, working style, and individual satisfaction in endogenously and exogenously formed teams. We randomly divide a sample of high school students into two groups: we assign students in one group to teams of varying gender composition using random assignment and we allow the students in the other group to form teams freely. We find that students form disproportionately more male-predominant teams that those that would be formed under random assignment and that students in endogenously-formed gender-biased teams prefer even more gender-biased teams ex-post. Our results also show that female-predominant teams under-perform other types of teams but these differences disappear when teams are endogenously-formed.
Keywords: J16; I21; I24; 330; team composition; gender; team formation; team dynamics; team performance; field experiment; decision-making